ON ORTHODOX/HETERODOX AND AUTISTIC/POST AUTISTIC ECONOMICS – A VIEW FROM THE ROMANIAN ACADEMIC LANDSCAPE - RODICA IANOLE; MIHAELA SANDU (Challenges of the Knowledge Society)
The way economics is perceived nowadays seems to be going back to the old label of `dismal science`, because it has not achieved to offer consistent and valid solutions to real problems in critical moments. In a constructive defense of our profession, we need to acknowledge the existence of some oversimplified hypothesis that do not conform to the actual human behavior, and thus to turn to different branches of the discipline (from behavioral to feminist, green economics and econo-physics, just to give some examples) that try to reintegrate economic thinking in the real landscape, through different approaches. The post autistic economics represents a powerful example within this attempt of offering economics a new spirit and new insights of how it should be taught and applied.The aim of this paper is to discuss on the multiple perspectives, orthodox and heterodox, autistic and postautistic, and on the manner they appear to be understood, accepted and implemented in the Romanian economic higher education. We question the neoclassical paradigm in search for new insights that could lead to a possible internal reform of the field, ppening it more to the opinions of the surrounding social sciences.